Midlands State University skill bundle - Taitia, Kudakwashe (Midlands State University, 2018)
Midlands’s State University Skill Bundle is a system documented in this project file, which deals with the bundling of student with skills in one web application. Skill Bundle exist to take advantage of the skills in the university from all parts of world through faculties and departments for students to share resources and skills instead without the involvement of any kind of currency. This document explains that the system will offer users a form of digital currency or points for free to exchange with some skill among students online. This in turn builds a one single platform, which is rich in skill and promotes the spread of quality skills and high education as well as return on creativity. This in return eliminates problems among students of lacking motivation due to low or little room for creativity among each other. Thus, this document shows how students utilize a chat space, which is known within the system for communication about their request made within the system.to clearly understand the concepts of this idea (Skill Bundle), reading further inside the document will elaborate to simplify the need and purpose of the system document as well as its functionality.